2016
DOI: 10.4172/2155-9899.1000420
|View full text |Cite
|
Sign up to set email alerts
|

Arg Deficiency Does not Influence the Course of Myelin Oligodendrocyte Glycoprotein (MOG35-55)-induced Experimental Autoimmune Encephalomyelitis

Abstract: Background: Inhibition of Abl kinases has an ameliorating effect on the rodent model for multiple sclerosis, experimental autoimmune encephalomyelitis, and arrests lymphocyte activation. The family of Abl kinases consists of the Abl1/Abl and Abl2/Arg tyrosine kinases. While the Abl kinase has been extensively studied in immune activation, roles for Arg are incompletely characterized. To investigate the role for Arg in experimental autoimmune encephalomyelitis, we studied disease development in Arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 27 publications
2
4
1
Order By: Relevance
“…Similar to the B-cell response in the Arg deficient mice, the T-cell response in vitro was not affected in the absence of Arg [14]. Taken together, these and previously reported data suggest that any functional consequences due to the absence of the Arg kinase in B-and T -lymphocyte activation, are rescued by the presence of c-Abl.…”
Section: The Role For Abl Kinases In B-cell Activationsupporting
confidence: 77%
See 4 more Smart Citations
“…Similar to the B-cell response in the Arg deficient mice, the T-cell response in vitro was not affected in the absence of Arg [14]. Taken together, these and previously reported data suggest that any functional consequences due to the absence of the Arg kinase in B-and T -lymphocyte activation, are rescued by the presence of c-Abl.…”
Section: The Role For Abl Kinases In B-cell Activationsupporting
confidence: 77%
“…The result was somewhat unexpected because of the previously demonstrated role for the Abl kinases in T-cell signaling and function [15], and we hypothesized that T lymphocyte activation, and thereby the autoimmune response, would be affected in the MOG35-55 immunized Arg -/-mice. In line with the EAE data, in vitro stimulation of T cells from the Arg deficient mice did not show an altered response compared to the Arg +/+ littermates [14]. We therefore concluded that the lack of Arg does not influence T cell activation, neither by MOG(35-55) peptide, mycobacteria, or Pertussis Toxin, which are all included in the induction of EAE, nor by activation of T lymphocytes in vitro.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations